Literature Review: Efektivitas Pengelolaan Dana BOS pada Sekolah Menengah Atas dan Kejuruan - Kharina Amadea Adiningrum; Lovia Putri Wulandari Sitanggang; Annisa Widi Selina; Atia Zahro (Teewan Journal Solutions, 2025)
School Operational Assistance (BOS) is one of the government policies aimed at supporting the implementation of basic and secondary education to be more effective and efficient through school operational funding. Therefore, the purpose of this study is to examine the effectiveness of BOS fund management in secondary and vocational schools through a systematic literature review. This study uses the Systematic Literature Review (SLR) method as descriptive qualitative research. Data were collected from various journals and articles published between 2020 and 2025, totaling 10 articles. In this literature analysis, it can be concluded that BOS management has generally been carried out in accordance with applicable technical guidelines, including budget planning based on priority scales, two-stage fund disbursement, supervision, and reporting involving various stakeholders. However, obstacles such as delays in fund disbursement, regulatory changes, and limited human resources remain major challenges that affect the effectiveness of BOS fund management. Transparency and accountability have proven to be key factors in improving the effectiveness of the use of these funds. This study recommends improving training for BOS managers and refining the fund disbursement mechanism to support the optimization of BOS fund usage to improve the quality of education at the secondary level.